Professional knowledge or motivation? Investigating the role of teachers’ expertise on the quality of technology-enhanced lesson plans - Backfisch, Iris; Lachner, Andreas; Hische, Christoff; Loose, Frank; Scheiter, Katharina (Learning and instruction, 2020)
In an expertise study with 94 mathematics teachers varying in their relative teacher expertise (i.e., student teachers, trainee teachers, in-service teachers), we examined effects of teachers' professional knowledge and motivational beliefs on their ability to integrate technology within a lesson plan scenario. Therefore, we assessed teachers' professional knowledge (i.e., content knowledge, pedagogical content knowledge, technological knowledge), and their motivational beliefs (i.e., self-efficacy, utility-value). Furthermore, teachers were asked to develop a lesson plan for introducing the Pythagorean theorem to secondary students. Lesson plans by advanced teachers (i.e., trainee teachers, in-service teachers) comprised higher levels of instructional quality and technology exploitation than the ones of novice teachers (i.e., pre-service teachers). The effect of expertise was mediated by teachers' perceived utility-value of educational technology, but not by their professional knowledge. These findings suggest that teachers’ motivational beliefs play a crucial role for effectively applying technology in mathematics instruction. •We examined effects of relative teacher expertise on the quality of technology-integration.•We used lesson plans to measure the quality of technology integration.•Relative teacher expertise accounted for quality of lesson plans.•Teachers utility-value mediated the relative teacher expertise effect.